A deterministic and logic model on small-world brain functional memory network. (1st January 2013) - Zhang, Lanhua; Tang, Yiyuan; Feng, Min; Han, Zhongdong; Xue, Shaowei
In order to understand the formation and evolution mechanisms of small-world characters in brain functional memory network visually and directly, we adopt the deterministic complex network modelling method to simulate the memory process and introduce the logic unit definition to decrease the complexity of the network. By the logic abstraction of memory node and edge, we setup the connection mechanism based on the memory anatomical characters and logic characters. Meanwhile, we introduce the logic memory cell definition meta-memory as the network node to setup the logic brain functional memory network in order to be more close to brain anatomical substrate and decrease the complexity of the transformation from large numbers of neurons to network node. We applied the deterministic modelling algorithm with set as data structure to make the simulation of the small-world characters memory network and got the data retrieval algorithm in accord with memory characters. The theoretical analysis and data simulation results imply that the deterministic and logic brain functional memory network has the small-world characters and it is feasible to model the brain functional memory network with deterministic modelling algorithm on the basis of memory cell by the logic definition of the meta-memory.